Preparative enantioseparation by supercritical fluid chromatography - Chen, Wenda (2010)
Supercritical fluid chromatography (SFC), due to its high throughput and efficiency, environmental friendliness, small solvent consumption, has been recognized as a powerful technique for enantioseparations. Preparative SFC is being increasingly used as a reliable method for rapidly accessing enantiopure compounds. To develop optimum methods for the SFC enantioseparation processes, a systematic study on the effect of different controllable parameters on process performance has been performed. The optimization for preparative SFC has been formulated as a multi-objective optimization problem to simultaneously maximize the productivity and minimize the solvent consumption. It has been solved using a proper mathematical model integrated with suitable optimization algorithm under different operating conditions, product quality requirements and elution fashion. In particular, isocratic and solvent gradient methods have been explored in detail and an attempt has been made to experimentally implement the results of the optimization study. Although some deviations in the experimental results were observed, the thesis quantitatively confirms the key advantages, significant reduction in solvent consumption at high productivity. The rigorous optimization techniques developed have a general application and can be used to objectively compare different techniques and provide a basis for rational scale-up of SFC process.